TINJAUAN ATAS FAKTOR-FAKTOR YANG MEMENGARUHI KAPASITAS JALUR KERETA API - Wiarco, Yuwono; Malkamah, Siti; Munthohar, Imam (FSTPT Indonesia, 2015)
Infrastructures should be planned and designed based on the required capacity in the future to provide good service. Methods of railway capacity that is commonly used in Indonesia is still adopted from other countries. It is then modified but it is currently still inefficiencies because operators have not dared to use to the fullest method of railway capacity. Therefore, the calculation methods of railway capacity should be reviewed and developed as well based on the reality in Indonesia. It is expected that the efficiency of railway operation system increases. The analysis was performed with the following steps; collecting the secondary data and the literature reviews. The results of the literature reviews stated that there are various factors that affect the railway capacity; the number of trains, heterogeneity, stability, speed, infrastructures, operation system, train length, time delay, junctions, intermediate signals, resources, scheduling, number of tracks, signal distance, termination, and maintenance. Based on the literature study, it is required further research on the development of the capacity calculation model for railway in Indonesia.